2019
DOI: 10.3390/toxins11120707
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Therapy Combined with Rehabilitation for Stroke: A Systematic Review of Effect on Motor Function

Abstract: Aim: The purpose of this study was to examine the effectiveness of botulinum toxin A (BoNT-A) therapy combined with rehabilitation on motor function in post-stroke patients. Methods: The following sources up to December 31, 2018, were searched from inception for articles in English: Pubmed, Scopus, CINAHL, Embase, PsycINFO, and CENTRAL. Trials using injections of BoNT-A for upper and lower limb rehabilitation were examined. We excluded studies that were not performed for rehabilitation or were not evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
1
24
0
1
Order By: Relevance
“…Although it is possible that BoNT therapy could improve motor function and motor control, a recent meta-analysis further explained that the failure of function improvement after BoNT therapy is mainly due to muscle weakness [ 53 ]. In a selected group of stroke survivors, it is likely that BoNT therapy in combination with adjuvant therapy to strengthen spastic muscles may help improve motor function [ 54 ]. In this study, the same amount of BoNT was injected to biceps muscles with moderate-to-severe spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible that BoNT therapy could improve motor function and motor control, a recent meta-analysis further explained that the failure of function improvement after BoNT therapy is mainly due to muscle weakness [ 53 ]. In a selected group of stroke survivors, it is likely that BoNT therapy in combination with adjuvant therapy to strengthen spastic muscles may help improve motor function [ 54 ]. In this study, the same amount of BoNT was injected to biceps muscles with moderate-to-severe spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Untreated, spasticity may lead to long-term secondary complications such as soft tissue contractures, decreased activities of daily living, pain, pressure sores, social isolation which all lead to decreased quality of life [ 4 , 5 , 6 ]. Botulinum toxin type A (BoNT-A) has been found to be effective and safe for treating focal post-stroke spasticity in the rehabilitation setting [ 7 ]. Several randomized and non-randomized controlled studies have documented the effectiveness of BoNT-A injections in reducing muscle tone in both the upper and lower limb in post-stroke spasticity [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] However, it was also reported to limited evidence for improving active arm function, but improving basic upper extremity tasks (e.g., facilitation of dressing, hand hygiene) and pain. [ 9 10 ] Meanwhile, Rosales et al reported the same results that BoNTA injection combined rehabilitation can provide a sustained reduction in early poststroke upper extremity spasticity, but arm and hand function were not affected. [ 11 ] Shaw et al [ 10 ] argued that agonist active weakness may be the critical factor rather than restriction by the spasticity.…”
Section: Discussionmentioning
confidence: 98%